Aplicación de prueba de jarras en las aguas del canal Latacunga-Salcedo-Ambato, a fin de disminuir la turbidez mediante floculantes en el periodo 2013 - Bautista Arias, Silvia Paulina (2014)
Canal irrigation Latacunga - Ambato -Salcedo is a linear structure approximately 32 km originates in the city of Latacunga of one of the main water sources in the province of Cotopaxi Pumacunchi Rio , which has executed this irrigation project that benefits three cities which named : Latacunga, Salcedo and Ambato, the project is executed in the form of direct feedback that is this type of water is not treated prior to any distribution.Within the total of beneficiaries comprises a total of 17,000 distributed in 63 irrigation irrigation boards located in both Cotopaxi and Tungurahua provinces and irrigation capacity caters to an average of 8,400 hectares. Among grasses, short rotation crops vegetables and fruit which are then marketed across the country .In addition to agricultural processes this water is used has been affected by the industrial growth of the two provinces and have made water a site direct download directly affecting irrigators and beneficiaries of this channel and after the population consume the products cultivated with groundwater....